Metaepistemic Injustice and Intellectual Disability: a Pluralist Account of Epistemic Agency - Catala, Amandine (Ethical Theory and Moral Practice, 2020)
The literature on epistemic injustice currently displays a logocentric or propositional bias that excludes people with intellectual disabilities from the scope of epistemic agency and the demands of epistemic justice. This paper develops an account of epistemic agency and injustice that is inclusive of both people with and people without intellectual disabilities. I begin by specifying the hitherto undertheorized notion of epistemic agency. I develop a broader, pluralist account of epistemic agency, which relies on a conception of knowledge that accounts not only for propositional knowing, but also for other types of knowing that have been largely neglected in debates on epistemic injustice and agency. Based on this pluralist account of epistemic agency, I then show that people with intellectual disabilities qualify as epistemic agents and therefore as subjects of epistemic justice. Finally, I argue that this pluralist account of epistemic agency pushes us to revisit the current conception of epistemic injustice and to expand its taxonomy in two important ways.
Keywords: EDI; agentivité épistémique; approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; handicap intellectuel; injustices épistémiques; inégalités; justice sociale; justice épistémique; philosophie; savoir propositionnel; sciences humaines; systèmes d'oppressions; taxonomie des savoirs; thématiques; violences; éthique

Par-delà les frontières du corps : repenser, refaire et revendiquer le corps dans le capitalisme tardif - Federici, Silvia ([Collection Cybernétique], 2020)
Comment reprendre corps? Comment nous rapporter au corps, cet objet éminemment historique, domestiqué, violenté, pathologisé? Silvia Federici répond: écoutons le langage du corps, sa fragilité et ses imperfections, afin de retrouver, par-delà ses frontières, la continuité magique qui nous relie aux autres êtres vivants qui peuplent la Terre. Mais surtout, identifions la plaie: les rapports sociaux de genre, de classe et de race. Dans cet ouvrage accessible et personnel, en dialogue avec les mouvements féministes contemporains, Silvia Federici entreprend d’extirper nos corps des pouvoirs et des dispositifs technologiques qui les aliènent et les transforment. Politiques de l’identité, chirurgie de transformation des corps, nouvelles technologies reproductives, ce livre examine avec lucidité ces questions brûlantes qui traversent le champ féministe.
Keywords: approches et analyses; corps; cours; discipline; fem3100; intersectionnalité; justice sociale; philosophie; premier cycle; rapports sociaux de sexe; sciences humaines; thématiques